2021
DOI: 10.1093/ofid/ofab416
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Resistance, Clinical Features, and Cytokine Profiles in Taiwanese Children With Mycoplasma pneumoniae Infection

Abstract: Background The factors to predict the progression of Mycoplasma pneumoniae infection remain inconclusive. Therefore, we investigated macrolide resistance prevalence, M. pneumoniae genotype, and clinical characteristics of childhood M. pneumoniae respiratory tract infections in Taiwan. Methods A total of 295 children hospitalized with respiratory tract infections with positive serological M. pneumoniae immunoglobulin M test re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…M. pneumoniae carry a total of 816,394 bp base pairs with 687 genes on the circulating double strands of DNA function to maintain their viability and reproduction [ 80 ]. Molecular epidemiology investigations of M. pneumoniae and macrolide susceptibility have been conducted in a wide range of geographical and temporal contexts [ 24 , 81 , 82 , 83 , 84 ]. Most investigations showed that MRMP usually had specific point mutations in the peptidyl transferase loop of 23S rRNA, as well as insertions or deletions in ribosomal proteins L4 and L22 [ 9 ].…”
Section: Prediction and Early Recognitionmentioning
confidence: 99%
“…M. pneumoniae carry a total of 816,394 bp base pairs with 687 genes on the circulating double strands of DNA function to maintain their viability and reproduction [ 80 ]. Molecular epidemiology investigations of M. pneumoniae and macrolide susceptibility have been conducted in a wide range of geographical and temporal contexts [ 24 , 81 , 82 , 83 , 84 ]. Most investigations showed that MRMP usually had specific point mutations in the peptidyl transferase loop of 23S rRNA, as well as insertions or deletions in ribosomal proteins L4 and L22 [ 9 ].…”
Section: Prediction and Early Recognitionmentioning
confidence: 99%
“… 1 Mycoplasma pneumoniae (MP) is a common cause of CAP in children and adolescents, accounting for about 10–30% of the cases. 2 , 3 MP infection can cause a variety of clinical symptoms, including fever, headache, cough, etc. 4 Several serious respiratory illnesses caused by MP have also been documented, such as pleural effusion, acute respiratory distress syndrome, and lung abscesses.…”
Section: Introductionmentioning
confidence: 99%